2016
DOI: 10.1097/aap.0000000000000420
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2-Chloroprocaine, Bupivacaine, and Lidocaine for Spinal Anesthesia in Patients Undergoing Knee Arthroscopy in an Outpatient Setting

Abstract: For spinal anesthesia in patients undergoing ambulatory knee arthroscopy, chloroprocaine has the shortest time to complete recovery of sensory and motor block compared with bupivacaine and lidocaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
34
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 33 publications
(37 reference statements)
8
34
1
Order By: Relevance
“…The full-text of 123 articles were evaluated, and then, 84 articles were excluded due to the following reasons: no results about the incidence of TNS (n = 42); no other local anesthetics were used (n = 18); conference posters (n = 7); abstracts only (n = 4); protocols (n = 4); healthy subjects (n = 4); non-randomized studies of intervention (n = 2); different anesthetic techniques between groups (n = 1); mixed spinal anesthetics (n = 1); and a brief report (n = 1). Therefore, a total of 39 RCTs were included in the final analysis ( Figure 1) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Descriptions Of Trialsmentioning
confidence: 99%
See 4 more Smart Citations
“…The full-text of 123 articles were evaluated, and then, 84 articles were excluded due to the following reasons: no results about the incidence of TNS (n = 42); no other local anesthetics were used (n = 18); conference posters (n = 7); abstracts only (n = 4); protocols (n = 4); healthy subjects (n = 4); non-randomized studies of intervention (n = 2); different anesthetic techniques between groups (n = 1); mixed spinal anesthetics (n = 1); and a brief report (n = 1). Therefore, a total of 39 RCTs were included in the final analysis ( Figure 1) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Descriptions Of Trialsmentioning
confidence: 99%
“…All these RCTs compared lidocaine with other local anesthetics (bupivacaine, prilocaine, mepivacaine, levobupivacaine, chloroprocaine, ropivacaine, procaine, articaine, or sameridine) and reported the incidence of TNS. We found that 28 RCTs had two groups [4][5][6][7][8][9][10][11][12]14,15,18,23,26,27,29,30,[34][35][36][37][38][39][40][41][42]44,46] of lidocaine more than other local anesthetics, while 11 RCTs had multiple groups [13,16,17,24,25,28,[31][32][33]43,45]. Five out of 11 RCTs have more than two lidocaine groups [16,24,28,33,43].…”
Section: Descriptions Of Trialsmentioning
confidence: 99%
See 3 more Smart Citations